2017
DOI: 10.4103/ijmpo.ijmpo_123_17
|View full text |Cite
|
Sign up to set email alerts
|

Analytical study on the efficacy of neoadjuvant chemotherapy using a combination of methotrexate, bleomycin, and cisplatin in the management of advanced squamous cell carcinoma of the buccal mucosa

Abstract: Context:Cancers of the buccal mucosa (CaBM) predominate in India with late- stage diagnosis and poor survival, necessitating optimal management. Aim: Our study aimed at testing the efficacy of combination neoadjuvant chemotherapy (NACT) using cisplatin (CIS), bleomycin (BL) and methotrexate (MTX) for reducing tumour volume prior to surgery.Methodology:Patients with advanced CaBM (stage III, IV, n = 100) were administered 6 rounds of NACT with CIS, BL and MTX. Responses, toxicity and 6-month follow-up was monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Adriamycin, an orally administered DNA alkylating agent, has been the most potent chemotherapy applied in clinic, in addition to surgical excision. Bleomycin had been emerged as another vital chemotherapeutic agent in many types of cancer, including Hodgkin lymphoma ( 7 ), testicular cancer ( 8 ), and squamous-cell carcinoma ( 9 ). In the previous study, we firstly identified salinomycin as a novel identified cancer stem cells (CSCs) killer in gastric cancer cells ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adriamycin, an orally administered DNA alkylating agent, has been the most potent chemotherapy applied in clinic, in addition to surgical excision. Bleomycin had been emerged as another vital chemotherapeutic agent in many types of cancer, including Hodgkin lymphoma ( 7 ), testicular cancer ( 8 ), and squamous-cell carcinoma ( 9 ). In the previous study, we firstly identified salinomycin as a novel identified cancer stem cells (CSCs) killer in gastric cancer cells ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is superior to single-agent with respect to response rate, duration of remission, and overall survival in patients with advanced and malignant urothelial carcinoma (4). Additionally, MTX/CPT is an effective regimen for patients with metastatic transitional cell carcinoma of the bladder and buccal mucosa (5,6). However, one of the primary concerns with the use of MTX/CPT is the possible development of toxicities including nephrotoxicity.…”
Section: Introductionmentioning
confidence: 99%